Investigação do comportamento de um sistema de transporte em massa usando simulação de eventos discretos e delineamento de experimentos - Hernandez, Maria Alejandra Guerrero (2014)
The problem of operations planning is particularly important for subway transportation systems planning; the accelerated growth of the cities; cannot be linearly followed by the infrastructure. This research is based in the discrete event simulation, of the variables headway (time between the train s exit from the platform), time for opening doors and speed involve at a massive transportation systems operation like the lines 1, 2 and 3 of the city of São Paulo, using discrete events simulation. This research had the goal of (1) understand their impact on the travel time of passengers, (2) the size of the queues on platforms, (3) the occupation of the train and the (3) waiting time before boarding. The computational model developed with the software ProModel, was accompanied by quantitative validation techniques, which ensure a statistical significance of 95% in the model results. The variables were analyzed with the basis of the methodology of design of experiments. This work allowed to find the most meaningful variables of the system and their relations to the type of demand line, this will lead to managers in taking decisions, it is possible to generate new strategies of operation in a short and medium term to improve transport efficiency, without the necessity in large investments within the infrastructure.